16 Reliability and efficiency of corneal thickness measurements using sterile donor tomography in the eye bank. (16th November 2022) - Hamon, Loïc; Quintin, Adrien; Mäurer, Stephanie; Weinstein, Isabel; Langenbucher, Achim; Seitz, Berthold; Daas, Loay
Abstract : Purpose: To evaluate the reliability and efficiency of sterile corneal thickness measurements of donor corneas stored in a plastic culture flask filled with organ culture medium I (MI) or II (MII) based on tomographic data using two different software: the built-in software of the anterior segment OCT (AS-OCT) and a MATLAB self-programmed software. Methods: Twenty-five (25) donor corneas (50%) stored in MI and 25 (50%) in MII were imaged 5 times consecutively using an AS-OCT. The central corneal thickness (CCT) was measured both with the manual measurement tool of the AS-OCT (=CCTm) and with a MATLAB self-programmed software allowing (semi-)automated analysis (=CCTa). We analyzed the reliability of CCTm and CCTa using Cronbach´s alpha (α) and Wilcoxon signed-rank test. Results: Concerning CCTm, 68 measurements (54.4%) in MI and 46 (36.8%) in MII presented distortions in the imaged 3D-volumes and were discarded. Concerning CCTa, 5 (4%) in MI and 1 (0.8%) in MII were not analyzable. The mean (± SD) CCTm was 1129 ± 6.8 in MI and 820 ± 5.1 µm in MII. The mean CCTa was 1149 ± 2.7 and 811 ± 2.4 µm, respectively. Both methods showed a high reliability with a Cronbach´s α for CCTm of 1.0 (MI/MII) and for CCTa of 0.99 (MI) and 1.0 (MII). Nevertheless, the mean SD of the 5 measurements was significantly higher for CCTm compared to CCTa in MI (p = 0.03), but not in MII (p = 0.92). Conclusions: Sterile donor tomography proves to be highly reliable for assessment of CCT with both methods. However, due to frequent distortions regarding the manual method, the (semi-)automated method seems to be more efficient and should be preferred.